Ultrasound imaging in patients with hip pain and suspected hip osteoarthritis: an inter-rater and intra-rater reliability study - Lene Terslev; Jan Hartvigsen; Ulrich Fredberg; Stine Clausen; Søren Kjær; Bodil Arnbak (BMJ Open)
Objectives The objectives of this study were to asses (1) inter-rater and intrarater reliability of ultrasound imaging in patients with hip osteoarthritis, and (2) agreement between ultrasound and X-ray findings of hip osteoarthritis using validated Outcome Measures in Rheumatology ultrasound definitions for pathology.Design An inter-rater and intrarater reliability study.Setting A single-centre study conducted at a regional hospital.Participants 50 patients >39 years of age referred for radiography due to hip pain and suspected hip osteoarthritis were included. Exclusion criteria were previous hip surgery in the painful hip, suspected fracture or malignant changes in the hip.Intervention Bilateral ultrasound examinations (n=92) were performed continuously by two experienced operators blinded to clinical information and other imaging findings. After 4–6 weeks, one operator reassessed the images. X-rays were assessed by a third imaging specialist.Primary and secondary outcome measures Inter-rater and intrarater reliability and agreement between ultrasound imaging and X-ray were assessed using Cohen’s ordinal kappa statistics for binary categorical variables and weighted kappa for ordered categorical variables.Results Kappa values (κ) for inter-rater reliability were 0.9 and 0.8 for hip effusion/synovitis and osteoarthritis grading, respectively. For acetabular and femoral osteophytes, femoral cartilage changes and labrum changes κ ranged from 0.4 to 0.7. Intrarater reliability had κ equal or higher compared with inter-rater reliability. Agreement between ultrasound and X-ray findings ranged from κ=0.2 to κ=0.5.Conclusion This study demonstrated substantial to almost perfect reliability on the most common ultrasound findings related to hip osteoarthritis and osteoarthritis grading. Agreement on the grade of osteoarthritis between ultrasound and X-ray was moderate. Overall, these results support ultrasound imaging as a reliable tool in the assessment of hip osteoarthritis.